Impact of baseline left ventricular ejection fraction and body mass index on the effect of 24-week Ipragliflozin treatment on left ventricular diastolic function in patients with type 2 diabetes and chronic kidney disease: insights from the PROCEED trial - Hiroki Teragawa; Atsushi Tanaka; Kanae Takahashi; Chikage Oshita; Yuko Uchimura; Nozomu Kamei; Hiroyuki Hirai; Michio Shimabukuro; Isao Taguchi; Yosuke Okada; Koichi Node (Cardiovascular Diabetology)
Abstract Background Sodium-glucose co-transporter 2 (SGLT2) inhibitors are important for treating patients with preserved left ventricular (LV) ejection fraction (LVEF). Several studies have assessed the effects of SGLT2 inhibitors on LV diastolic function, with conflicting results. In this sub-analysis of the Program of Ipragliflozin for Endothelial Dysfunction in Chronic Kidney Disease and Type 2 Diabetes (PROCEED) trial—including patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD)—we examined the effect of ipragliflozin compared with non-SGLT2 inhibitor standard therapy (control) on changes in the maximum early diastolic velocity to average early diastolic peak velocity (E/e’) ratio (an index of LV diastolic function) via echocardiography. Methods Of the entire PROCEED trial dataset, 57 participants (ipragliflozin group, n = 28; control group, n = 29) with available echocardiography data at baseline and 24 weeks were included. The primary endpoint was the change in the E/e’ ratio from baseline to 24 weeks. The effect of SGLT2 inhibitors on the endpoint was stratified by baseline LVEF, body mass index (BMI), N-terminal pro-brain natriuretic peptide (NT-proBNP) level, estimated glomerular filtration rate (eGFR), and urine albumin-to-creatinine ratio (UACR). Results No significant difference in the E/e’ ratio changes was observed between the ipragliflozin and control groups (group difference: − 0.82 [95% CI: − 2.44 to 0.81]; P = 0.317). The E/e’ ratio was unaffected by baseline NT-proBNP, eGFR, and UACR levels. However, ipragliflozin significantly reduced the E/e’ ratio in patients with LVEF ≥ 60% (n = 21, group difference: − 1.42 [− 2.76 to − 0.08]; P = 0.038) or BMI ≥ 25 kg/m2 (n = 19, group difference: − 1.95 [− 3.56 to − 0.34]; P = 0.020), but not in those with LVEF < 60% (n = 7, group difference: 1.83 [− 4.48 to 8.14]; P = 0.527) or BMI < 25 kg/m2 (n = 9, group difference: 1.34 [− 1.65 to 4.34]; P = 0.363). Significant interactions were noted between patients with LVEF ≥ 60% and < 60% (P for interaction=0.048) and BMI ≥ 25 kg/m2 and < 25 kg/m2 (P for interaction=0.016). Conclusions In subgroups with higher LVEF and BMI, ipragliflozin improved diastolic function more than standard treatment. These results may partly support the beneficial effect of SGLT2 inhibitors on LV diastolic performance.